2007
DOI: 10.1508/cytologia.72.111
|View full text |Cite
|
Sign up to set email alerts
|

Crossability and Characterization of Interspecific Hybrids between Sexual Pennisetum glaucum (Pearl Millet) and a New Cytotype (2n=56) of Apomictic P. squamulatum

Abstract: Summary Pennisetum squamulatum is an important species belonging to tertiary gene pool of cultivated pearl millet as potential donor of several genes. Recently a new cytotype with 2nϭ56 chromosmes has been identified. Crossability of this cytotype has been studied with diploid and induced tetraploid pearl millet. The hybrids produced with this novel cytotype were compared for their characteristics with the hybrids previously reported with widely reported 2nϭ54 P. squamulatum cytotypes. Strong incompatability b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Cytological studies on F 1 hybrids involving P. glaucum (4x) and P. squamulatum 2nϭ56 (8x?) supported the view on this species being octoploid based on xϭ7 (Kaushal et al 2007). Had the species been a hexaploid, the contribution of P. squamulatum in its F 1 hybrid with 4x, P. glaucum, would be a triploid gamete that will not show a near normal meiotic system with predominant bivalent associations and higher fertility, as observed by the present workers.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Cytological studies on F 1 hybrids involving P. glaucum (4x) and P. squamulatum 2nϭ56 (8x?) supported the view on this species being octoploid based on xϭ7 (Kaushal et al 2007). Had the species been a hexaploid, the contribution of P. squamulatum in its F 1 hybrid with 4x, P. glaucum, would be a triploid gamete that will not show a near normal meiotic system with predominant bivalent associations and higher fertility, as observed by the present workers.…”
Section: Discussionsupporting
confidence: 89%
“…The present studies on crossability of P. squamulatum with P. glaucum together with earlier reports (Dujardin and Hanna 1983, Kaushal et al 2007, Marchais and Tostain 1997, it is clear that P. squamulatum hybridizes easily with P. glaucum when the chromosome number of latter is doubled (2nϭ4xϭ28). The success of the cross is an ample indication that the two species are close enough and only barriers to crossability is the difference in ploidy level between the two species, and not the basic chromosome number (accounting for Endosperm Balance Number (EBN) considerations).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Interspecific hybrids (F 1 s and advanced back-cross generations) involving pearl millet were produced with P. orientale (Patil and Singh 1964;Hanna and Dujardin 1982;Hanna 1983a, 1984a;Zadoo and Singh 1986), as well as with P. squamulatum Hanna 1983b, 1985;Kaushal et al 2007) in a view to improve genepool, study inheritance of apomixis and to determine their cytotaxonomic relationships with pearl millet. Cytogenetic studies on interspecific hybrids revealed limited affinity of chromosomes of these two species with pearl millet.…”
mentioning
confidence: 99%